Determining Public Perception On Street Art Through Descriptive Data Analysis - Qistina Donna, Lee Abdullah; Salmiah, Abdul Hamid; Aliffazraie, Jali; Jimmy, Salau (The International Journal of Innovative Design, Creativity and Social Sciences (IJIDeCS), 2018)
This paper presents a frequency and descriptive testing on public perception of street art in preserving Malaysian culture. Street art has emerged as a new form of public art which starting to gain attention in different countries around the world, including Malaysia. Street art creates a new phenomenon to the country’s, especially the main cities’ interactivity and vitality such as Kuala Lumpur and Pulau Pinang. As it is still considerably new in Malaysia, there has not been many local studies that examine the preservation of Malaysian culture through street art or its potential as a creative medium in enhancing people’s experience. Based on case studies conducted in Georgetown, Laman Seni, and Kuching, this study aims to explore people’s perception of street art in preserving the Malaysian culture. The sample size for the study was 384 samples whereby the respondents are aged 20 years old and above. The data will by and large represent the perceived value of public appreciation towards the street arts in Malaysia.